PPARs in Regulation of Paraoxonases: Control of Oxidative Stress and Inflammation Pathways - Jordi Camps; Anabel García-Heredia; Anna Rull; Carlos Alonso-Villaverde; Gerard Aragonès; Raúl Beltrán-Debón; Esther Rodríguez-Gallego; Jorge Joven (PPAR Research)
The paraoxonase (PON) group of enzymes, composed of PON1, PON2, and PON3, play an important role in decreasing oxidative stress by degrading lipid peroxides. PON1 synthesis is upregulated by PPAR. Several pharmacological compounds (acting as antioxidants and, hence, atheroprotective) stimulate both PPAR activity and PON1 expression. Recent evidence suggests that PON1 and the monocyte chemoattractant protein-1 (MCP-1) are involved in coordinating the inflammatory response in damaged tissues; PPAR may be central in the regulation of these biochemical pathways. This article reviews the state of knowledge on PON1 biochemistry and function, the influence of genetic variation, and the regulation of PON1 expression by pharmaceutical compounds that increase PPAR activity. We also describe recent lines of evidence suggesting links between PON1 and MCP-1 and how their production may be regulated by PPAR.